Analisis Pengaruh Bauran Pemasaran terhadap Keputusan Pembelian Konsumen pada Produk Sayuran Organik (Studi Kasus Super Indo Q Square Bogor) - Kemuning, Larasati; Yusiana, Ekalia; Budiandrian, Bayu (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2024)
Super Indo Q Square in Bogor Regency is one of the Super Indo branches, a retail company established since 1997. To maintain competitive advantage, the company employs a marketing mix strategy encompassing price, product, promotion, location, people, process, and physical evidence. This study aims to examine the impact of this marketing mix on consumer purchasing decisions and satisfaction levels. The research method employed accidental sampling with 100 respondents, gathering both primary and secondary data through questionnaires, observations, interviews, and literature reviews. Data analysis utilized Multiple Linear Regression, Importance Performance Analysis (IPA), and Customer Satisfaction Index (CSI). The results indicate that (1) Price, product, location, people, process, and physical evidence significantly influence consumer purchasing decisions. (2) The level of customer satisfaction at Super Indo Q Square Bogor reached 83,82%, It shows a high level of satisfaction and the results of the total level of conformity obtained from all dimensions of 93%, meaning that the conformity value is still insufficient to reach 100%.